Intra-abdominal seminoma in undescended testis with retroperitoneal nodal metastasis: A case report - Ranjan Kumar Patel,; Hitesh Sarda, (Indian Journal of Case Reports, 2021)
Undescended testis or cryptorchidism is the most common predisposing factor in the development of testicular germ cell tumors with seminoma being the most common type. Therefore, testicular malignancy should be ruled out in case of an abdominal mass in a cryptorchid patient. Here, we present a case of intra-abdominal seminoma transformation of the undescended right testis with retroperitoneal nodal metastasis in a 54-year-old male which was clinically manifested as a gradually enlarging intra-abdominal mass and dull aching lower abdominal pain. He was managed with surgical removal, followed by chemotherapy.